Clinical consult to psychiatric nursing for advanced practice - Rhoads, Jacqueline, 1948-; Murphy, Patrick J. M. (New Yorkm NY : Springer Publishing Company, 2015)
This is the only advanced practice guide to provide an overview of the major DSM-5 disorders across the lifespan and complete clinical guidelines for their psychopharmacologic management. It has been compiled by expert practitioners in psychiatric care and is designed for use by nurse practitioners and other primary caregivers in clinical practice. The guide is organized in an easy-to-access format with disorders for which drugs can play a significant therapeutic role. The listing for each disorder includes clinical features and symptoms, as well as information about the most current and effec.
The psychiatric interview and diagnosis -- Psychotherapeutic management -- Behavioral therapy, cognitive behavioral therapy, and psychoanalysis -- Clinical neuroanatomy of the brain -- The relationship of psychopharmacology to neurotransmitters, receptors, signal transduction, and second messengers -- Principles of pharmacokinetics and pharmacodynamics -- Principles and management of psychiatric emergencies -- Behavioral and psychological disorders in the elderly -- Substance use disorders -- Psychotic disorders -- Mood disorders -- Anxiety disorders -- Somatic symptom and related disorders -- Dissociative disorders -- Sexual dysfunction -- Paraphilic disorders -- Feeding and eating disorders -- Personality disorders -- Sleep disorders -- Disorders presenting in infancy or early childhood (0-5 years of age) -- Disorders presenting in middle childhood (6-11 years of age) oradolescence (12-18 years of age).
Includes bibliographical references and index.
Online resource; title from electronic title page (ebrary, viewed on June 22, 2015).
English.
WorldCat record variable field(s) change: 650
Keywords: Psychiatric nursing; Psychology, Pathological; Psychotropic drugs; Psychopharmacology; Mental illness -- Treatment; Mental Disorders -- nursing; Mental Disorders -- therapy; Psychiatric Nursing -- methods; Psychopharmacology -- methods; Psychopathology; Psychotropic Drugs; Psychopharmacology; Psychopathologie; Psychotropes; Psychopharmacologie; Maladies mentales -- Traitement; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Psychiatric nursing; Psychology, Pathological; Psychopharmacology; Psychotropic drugs; Electronic books; Electronic books